Oral Presentations Abstracts: ETHICAL ASPECTS OF USING VIRTUAL REALITY IN PSYCHIATRY - ISAILĂ, Oana Maria; HOSTIUC, Sorin; CURCĂ, Filip; CURCĂ, George Cristian (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Virtual reality (VR), initially a form of entertainment has begun to find its way in healthcare practice. One of its main areas of interest is the treatment of psychiatric disorders. When using VR, the basic ethical principles underlying the physician-patient relationship should be respected, but they should be customized by the presence of an additional layer of complexity generated by the interposition of the virtual world. The physician-patient relationship is often multidirectional, often including a larger team of healthcare professionals, family members or acquaintances, working conjointly to optimize the medical care. Each time other participants are involved within this relationship, the complexity of the ethical issues tends to increase. For example, if the patient has decreased insight, it is possible that other persons must make some medical decisions – resulting a prioritization of beneficence compared to autonomy. Also, we must take into account the fact that many psychiatric symptoms can be seen as a form of “virtual reality” by the patient. The healthcare provider must take additional safety measures to minimize the harms made by VR techniques in psychiatric patients, by using methods that are individually tailored. The main aim of this paper is to debate the ethical aspects surrounding the applicability of virtual reality in treating psychiatric patients, with an emphasis on the elements that were mentioned earlier.